TUNTUTAN PEKERJAAN DAN INTENSI PENSIUN DINI - Annisa Okiwianti; Annisaa Miranty Nurendra (PSIKODIMENSIA, 2017)
This research aims to test the correlation between job demand and early retirement intention. The hypothesis in this study is that there is a positive relation between the job demand and early retirement intention. Respondents in this research are 50 employees of a ministry, consist of male and female employee aged 40 to 54 years old. Job demand scale used in this research is the modification of JD-R scale developed by Jackson and Rothman (2005). The modification based on three aspects of the job demand by Schaufeli and Bakker (2004). The scale of early retirement intention was developed by the researchers based on the aspect of intention by Ajzen (2005). The result indicated that there is no correlation between job demand and early retirement intention (r = -0.038, p = 0.397).